Comparative evaluation of anxiety levels among adult patients undergoing dental treatment in pediatric and conventional operatory: a randomised clinical trial - Kulkarni, Poorva; Hugar, Shivayogi M.; Bhusari, Bhuvanesh N.; Bagewadi, Anjana; Desai, Samruddhi; Hugar, Shweta (International Journal Of Community Medicine And Public Health, 2024)
Background: Individuals of all ages often experience anxiety before undergoing dental procedures. Therefore, it's crucial for dentists to create a calming operatory environment with distraction techniques to help alleviate adult patient anxiety. This clinical trial evaluated adult patient anxiety in both conventional and pediatric operatory rooms. Methods: This prospective split-mouth randomized controlled clinical trial was 11 conducted between November 2023 and April 2024. Twenty-four adult patients (13 females and 11 12 males) with a mean age of 37±4.53 years participated in this study. Each participant (n=24) received 13 both conventional and pediatric operatory. Pre- and post-operative pulse rates and anxiety scores 14 were measured using a pulse oximeter and modified Corah’s dental anxiety scale, respectively, in both 15 operatory rooms. Results: The study found a statistically significant decrease in both pulse rate and anxiety scores post-operatively in both operatory settings (p<0.05). However, the reduction in anxiety was more pronounced in the pediatric operatory compared to the conventional operatory (p=0.0433). Participants reported greater comfort and reduced anxiety in the pediatric setting, with 83% favoring its vibrant ambiance and 87% feeling less anxious after treatment in this environment. Conclusions: The vibrant environment of a pediatric dentistry operatory, featuring colorful walls, television, music, and other engaging elements can serve as a more effective for reducing anxiety compared to the plain and monotonous ambiance of the operatory.